Nonmesonic weak decay of Λ hypernuclei: The ΛN - ΣN coupling - Bauer, Eduardo (2017)
The nonmesonic weak decay of Λ hypernuclei is studied within a microscopic diagrammatic approach which is extended to include the ΛN - ΣN strong interaction coupling. We adopt a nuclear matter formalism which, through the local density approximation, allows us to model finite hypernuclei. One-meson-exchange potentials are used for the weak and strong four-baryon interactions. The rates for the neutron- and proton-induced weak decays, ΛN → nN and ΛN → ΣN → nN (N = n or p; Σ = Σ⁻, Σ⁰, and Σ⁺), are predicted for Λ¹²C, Λ²⁸Si, Λ⁵⁶Fe, and Λ²⁰⁸Pb. The ΛN - ΣN coupling turns out to provide a contribution of about 23% (5%) to the total neutron-induced rate (proton-induced rate). Again as an effect of the hyperon coupling, the total one-nucleon-induced rate increases by about 9%, while the Γn/Γp ratio increases by about 17%. The saturation property of the nonmesonic rates with increasing hypernuclear mass number is clearly obtained and explained. The above percentage modifications remain almost unaltered through the hypernuclear mass number. All the non-negligible changes introduced by the ΛN - ΣN coupling lead to a definite improvement of our predictions once compared with the available KEK and FINUDA data.